The Influence of Profitability, Liquidity, and Operating Capacity on Financial Distress with Capital Structure as a Moderating Variable - Ekaviana, Dessy (Politeknik Keuangan Negara STAN, 2024)
The aim of this research is to determine the effect of profitability, liquidity and operating capacity on financial distress with capital structure as a moderating variable. The population used in this research is manufacturing companies registered on the IDX in 2020-2022, totaling 90 companies using purposive sampling techniques to obtain 256 units of research sample data. This data was obtained from the annual financial report on the IDX. The analytical method used is logistic regression analysis with SPSS 25 software. This research uses three independent variables, namely profitability, liquidity and operating capacity, which were chosen based on inconsistent findings from previous research. The innovation in this research lies in the addition of Capital Structure as a moderating variable, with a proxy for debt to equity ratio (DER). This step was taken because there was little previous research that treated Capital Structure as a moderating variable. The use of DER is expected to strengthen or weaken the relationship between profitability, liquidity and operating capacity and financial distress. The research object includes manufacturing companies listed on the IDX, with an observation period from 2020 to 2022.